Insights into Evolutionary Relationships of Proboscis Monkeys Using In Silico Mitochondrial DNA Analysis - Rani Sasmita; Badruzsaufari Badruzsaufari; Intan Widya Pangestika (Biocaster : Jurnal Kajian Biologi, 2026)
This study investigates the evolutionary position of the proboscis monkey (Nasalis larvatus) within the Colobinae subfamily using in silico phylogenetic analysis of three mitochondrial protein-coding genes (COI, COII, and COIII). Seventy sequences retrieved from GenBank were aligned and analyzed using the Maximum Likelihood method with 1,000 bootstrap replicates. All genes exhibited conserved lengths and strong AT bias (59,21-60,68%), reflecting typical mitochondrial genome characteristics shaped by asymmetric replication and purifying selection. Genetic distance analyses revealed high intraspecific consistency in Nasalis larvatus, while demonstrating marker dependent variation in phylogenetic resolution. COII and COIII provided clearer intergeneric separation compared to the more conserved COI marker. Phylogenetic reconstruction showed topological variation among markers, however, a consistent evolutionary signal emerged, with Nasalis larvatus clustering robustly with Simias concolor across all gene trees. This pattern supports the monophyly of the odd nosed monkey clade and aligns with genome scale phylogenomic evidence. Overall, this study highlights the limitations of single gene analyses and emphasizes the importance of multi marker or genome scale approaches for resolving complex evolutionary relationships. These findings provide foundational insights into the evolutionary history of Nasalis larvatus and reinforce the relevance of mitochondrial markers in primate conservation genetics.